Análise aguda dos marcadores mecânicos da fadiga em diferentes métodos de treino no powerlifting paralímpico - Mota, Márcio Getirana (2022)
Introduction: In Brazilian society and in the world, a great search for high performance sports is noticeable. Within this perspective, the Paralympic modalities have been gaining prominence. The growing number of Paralympic athletes with each cycle of the games only increases, great records were broken at the London 2012 Paralympics, from broadcasts, audiences, public as well as in sports performance. The benefits of sports practice for people with disabilities are already well disseminated in society, the training routine promotes numerous benefits as well as some degree of risk of injury. Objective: The objective of this study was to evaluate the neuromuscular indicators of fatigue in two different training methods: isoinertial and eccentric in the adapted bench press in Paralympic powerlifting athletes. Methods: Eleven male Paralympic powerlifting athletes (age 31.54±9.72; body weight 73.63±17.55; 1RM 121.63±40.94) were evaluated to measure neuromuscular fatigue. Fatigue was measured in five moments through the average propulsive velocity - MPV, Pre-intervention (average of the MPV of three repetitions at 45% of the 1RM), intervention (average of the MPV of the five repetitions during five sets at a load of 80% of the 1RM for TRAD and 110%-80% of 1RM for ECC), post-intervention (average of three repetitions MPV at 45% of 1RM) 24h after the training session (average of three repetitions MPV at 45% of 1RM) and 48h after the training session (average of the MPV of three repetitions at 45% of the 1RM). For the intervention, 5 sets of 5 repetitions were used for both workouts. Results: Traditional training did not present neuromuscular fatigue in any of the analyzed moments. In relation to eccentric training, there is a significant reduction in PMV pre and post training: ECC (0.85 m/s ± 0.21, 95% CI 0.70-0.99; vs. 0.72 m/s ± 0.20, 95% CI 0.59-0.86, respectively, p=0.002, F(1,10)=3,310, η2p=0,249 - average effect). There was also a difference between TRAD and ECC training after intervention (0.87 m/s ± 0.22, 95%CI 0.72-1.02 vs. 0.72 ± 0.20, 95%CI 0.59-0.86 p=0.042, F(3.30)=10.190, η2p =0.505 - very high effect). During the training sets, the loss of MPV in set “1” was significant between traditional and eccentric training (15.46 m/s ± 3.64%, 95%CI 13.02-17.90 vs. 27.55 m/s ± 3.64%, 95%CI 13.02-17.90 vs. 12.21%, 95%CI 19.34-35.76, respectively, p=0.003) and in the series "3" between the TRAD (17.12 m/s ±6.78%, 95%CI 12.56-21 .67) and ECC (25.72 m/s ±10.38%, 95%CI 18.75-32.69, p=0.041). In both series, F(1,10)=22,762, η2p=0,695 (Very high effect). Conclusion: after the observed results, Coaches and Paralympic Powerlifting competitors should be cautious in using only the VMP as an indicator of neuromuscular fatigue for strength competitors. because when performing five sets of five repetitions at 80% of the 1 RM, neuromuscular fatigue was not observed.